Alginate Particles as Platform for Drug Delivery by the Oral Route: State-of-the-Art. (8th April 2014) - Sosnik, Alejandro
Abstract : Pharmaceutical research and development aims to design products with ensured safety, quality, and efficacy to treat disease. To make the process more rational, coherent, efficient, and cost-effective, the field of Pharmaceutical Materials Science has emerged as the systematic study of the physicochemical properties and behavior of materials of pharmaceutical interest in relation to product performance. The oral route is the most patient preferred for drug administration. The presence of a mucus layer that covers the entire gastrointestinal tract has been exploited to expand the use of the oral route by developing a mucoadhesive drug delivery system that showed a prolonged residence time. Alginic acid and sodium and potassium alginates have emerged as one of the most extensively explored mucoadhesive biomaterials owing to very good cytocompatibility and biocompatibility, biodegradation, sol-gel transition properties, and chemical versatility that make possible further modifications to tailor their properties. The present review overviews the most relevant applications of alginate microparticles and nanoparticles for drug administration by the oral route and discusses the perspectives of this biomaterial in the future.